Risk of Environmental Exposure to H7N9 Influenza Virus via Airborne and Surface Routes in a Live Poultry Market in Hebei, China - Zhang, Cheng; Guo, Kangkang; Cui, Huan; Chen, Ligong; Zhang, Chunmao; Wang, Xuejing; Li, Jiaming; Fu, Yingying; Wang, Zhongyi; Guo, Zhendong; Liu, Juxiang; Dong, Shishan (Frontiers in Cellular and Infection Microbiology, 2021)
Environmental transmission of virus to human beings has become an emergency warning of potential epidemic outbreak, such as SARS-CoV-2 and influenza virus. Recently, a H7N9 virus, A/environment/Hebei/621/2019(H7N9), was isolated by environmental swabs from a live poultry market in Hebei, China. We found that it could transmit by direct contact and aerosol in mammals. More importantly, after 5 times passages in mice, it showed two adaptive mutations, PB1-H115Q and B2-E627K, exhibiting an increased virulence and aerosol transmissibility. Those results suggested that this H7N9 virus might potentially transmit between human beings through environmental or airborne routes.